Porphyromonas Gingivalisin Different Peri-Implant Conditions: a Pilot Cross - Sectional Study - Nikolija Savčić; Damir Henjaš; Marija Jezdić; Ana Đinić Krasavčević; Iva Milinković (Acta Stomatologica Croatica, 2022)
Objective: To assess the potential correlation between clinical peri-implant parameters and the presence of Porphyromonas gingivalis in different peri-implant conditions. Material and methods: The study included 30 patients from the Department of Periodontology and Oral Medicine divided into three equal groups, defined according to the following diagnoses: peri-implantitis (PI), peri-implant mucositis (PM), and peri-implant health (HI). Clinical parameters such as peri-implant probing depth (PPD), bleeding on probing (BOP), suppuration on probing (SUP), and plaque index (PI) were recorded. The samples of peri-implant crevicular fluid were collected and relative levels of Porphyromonas gingivalis were analyzed using Real-Time PCR (Reverse transcriptase – real-time polymerase chain reaction). Results: The mean patient age was 51.33 ± 12.61 years. The mean value for Porphyromonas ginigvalis relative level was higher in the PI group (14.80 ±31.51) compared to PM and HI group (0.48 ± 1.34 and 0.06 ± 0.12, respectively). This parameter significantly differed between PI and HI (p=0.012), as well as PI and PM (p=0.049). The mean whole mouth probing pocket depth (PPD) in the PI group (4.02mm ± 0.77mm) was also significantly greater compared to the other two groups (3.39mm ± 0.52mm in PM and 1.97mm ± 0.54mm in the HI group. The SUP in the PI (mean value of 18%) group was more frequent than in PM (mean value of 14%) while the SUP was not detected in the HI group. The correlation between clinical parameters and relative levels of Porphyromonas gingivalis was not significant. Conclusions: The findings of this research indicate higher relative levels of Porphyromonas gingivalis in peri-implant lesions, especially in peri-implantitis.